Changing the theoretical centre in the ethics of justice: from humanity to life - Ramírez Martínez, María Teresa (2021)
The subject of justice has had as its theoretical center human relations, this approach starts from an anthropocentric parameter, which has excluded from his study other forms of life. An analysis of the unequal and destructive consequences of this paradigm is presented. The objective is to contrast various philosophical models that address the importance of including non-human beings within the ethical study of justice, to conclude in a proposal that allows the inclusion of biodiversity. The theories of Cortina, Vandana Shiva, Naess, Gudynas, Singer and Nussbaum are taken up. Consequently, it is impossible to continue with anthropocentrism, the change to a theoretical model based on inclusive justice is proposed. The analysis and comparison of authors is used as a method to find convergences and divergences between them, which allows expanding the research to be able to contextualize each theoretical posture.